Demand and motivation for influenza vaccination among healthcare workers before and during the COVID-19 era: a cross-sectional survey - Štěpánek, Ladislav; Nakládalová, Marie; Vildová, Helena; Boriková, Alena; Janošíková, Magdaléna; Ivanová, Kateřina (Human vaccines & immunotherapeutics, 2021)
Protection of healthcare workers (HCWs) against influenza is essential for patient health and a functional health system. The study aimed to analyze the demand for seasonal influenza vaccination (SIV) among various groups of HCWs in a tertiary care hospital before and during the COVID-19 pandemic and to identify their motives for this season's SIV. Before this influenza season (2020/21), the hospital management offered free SIV to all HCWs and promoted it on the internal network. Out of 4,167 HCWs, 630 HCWs expressed interest in SIV and were vaccinated in the hospital. They filled in a total of 603 self-administered pen-and-paper questionnaires. The mean age of the respondents (374 females and 229 males) was 45 ± 12 years. Physicians accounted for 48% of the vaccinated persons but for only 24% (p < .001) of all HCWs to whom SIV was offered. Only 16% of respondents vaccinated this year also received SIV before the last season (2019/20), with the proportion of physicians (19%) being statistically significantly higher than that of non-physicians (13%, p = .045) and the proportion of chronically ill HCWs (22%) being higher than that of healthy individuals (13%, p = .004). Most frequently, respondents' motivation to get vaccinated this year was self-protection (61%), that is concerns about contracting influenza together with COVID-19 or alone, followed by family protection (58%) and patient protection (53%). In conclusion, COVID-19 contributed to an increased demand for SIV among HCWs and the threat of contracting it together with influenza was the most frequent motive.
Keywords: pandemie; Pandemics; mužské pohlaví; Male; Surveys and Questionnaires; Female; Humans; Attitude of Health Personnel; Influenza Vaccines; vakcíny proti chřipce; motivace; lidé; motivation; COVID-19; Cross-Sectional Studies; Middle Aged; ženské pohlaví; lidé středního věku; Seasonal influenza vaccination; Health Personnel; healthcare worker; průzkumy a dotazníky; Motivation; vakcinace; SARS-CoV-2; Influenza, Human; zdravotnický personál; dospělí; chřipka lidská; Adult; Vaccination; průřezové studie; self-protection; postoj zdravotnického personálu